A scaling and numerical analysis of the effects of natural convection when Sal’nikov’s reaction: P → A → B occurs, together with diffusion and heat transfer in a spherical batch reactor - A. N. Campbell; S. S. S. Cardoso; A. N. Hayhurst (ՀՀ ԳԱԱ հրատ.)
Sal’nikov’s reaction: P → A → B involves a precursor, P, in two consecutive, first-order chemical reactions, yielding a final product B via an intermediate A. Partly as an academic exercise, but partly because of its relationship with cool flames, the situation is considered where the second step is faster than the first one, which is taken to be thermoneutral without an activation energy. The second step is assumed to have a significant activation energy, although it is exothermic. The reaction proceeds batchwise inside a spherical reactor, whose walls are held at a constant temperature, but do not participate chemically. The subsequent behaviour of the system depends on the interaction between convection, diffusion of heat and mass, and chemical kinetics.
Keywords: Քիմիա